Intergenerational Arabic Learning: Rethinking Grammar Instruction Through Adaptive Design - Iqlima Najmi Amalia Anandiar; Maman Abdurahman; Mia Nurmala (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
The study of Arabic grammar within mixed-age classrooms has become an increasingly observable phenomenon in contemporary language learning settings. This intergenerational composition creates a distinctive instructional environment that presents both unique challenges and meaningful opportunities for Arabic language educators. This study explores how learning unfolds and how teachers manage and respond to the diverse classroom composition. Using a qualitative case study design, data were collected through classroom observations, and in-depth interviews with teachers, learners, and administrators, complemented by document analysis. The data were analyzed thematically using Instructional Design Theory (IDT) as the analytical framework. Findings reveal that the age-diverse learning environment brings variations in individual needs and motivations, which are actively accommodated through an adaptive learning cycle. In this cycle, strategies are continuously adjusted in response to students’ needs and interactions, ensuring dynamic and effective classroom engagement. This study represents one of the earliest efforts in Indonesia to explore the dynamics of mixed-age Arabic language learning, providing valuable insights for designing and managing instruction in age-diverse classrooms. The findings not only offer practical pedagogical guidance for educators but also establish a foundational framework for future scholarship on intergenerational learning within Arabic language education.